A nanoplasmonic probe as a triple channel colorimetric sensor array for protein discrimination. Issue 13 (27th May 2016) - Mao, Jinpeng; Lu, Yuexiang; Chang, Ning; Yang, Jiaoe; Yang, Jiacheng; Zhang, Sichun; Liu, Yueying
Abstract : The salt-induced aggregation, nanoparticle regrowth and self-assembly behaviors of gold nanoparticles (AuNPs) and DNA conjugates could be changed after interaction with different proteins, generating various color changes and a unique fingerprint pattern for each protein. Abstract : The salt-induced aggregation, nanoparticle regrowth and self-assembly behaviors of gold nanoparticles (AuNPs) and DNA conjugates could be changed after interaction with different proteins, generating various color changes and a unique fingerprint pattern for each protein. The triple-channel colorimetric signals have been employed for protein discrimination with the naked eye.